Genetic variability of traits of the laticiferous system and association with rubber yield in juvenile and adult rubber tree progenies - Gouvêa, Lígia Regina Lima; Moraes, Mario Luíz Teixeira de [UNESP]; Gonçalves, Elaine Cristine Piffer; de Moraes, Marcela Aparecida [UNESP]; Gonçalves, Paulo (Elsevier, 2022)
The objectives of this study were to investigate genetic variation and association of the traits of the laticiferous system with rubber yield in young and adult rubber tree progenies Hevea brasiliensis, and compare the traits of the laticiferous system at different heights of the adult trees. The genetic material is composed of progenies from open pollination from the rubber tree breeding program of IAC, evaluated in the experimental field of UNESP in Ilha Solteira, SP, Brazil, in the young and adult phases, and in the Polo Regional Alta Mogiana of the Agência Paulista de Tecnologia do Agronegócio in Colina, SP, Brazil in the young phase. A randomized block experimental design was used with 30 treatments (progenies), three replications, and 10 plants per plot. The following traits were evaluated: rubber yield (RY), virgin bark thickness (BT), number of rings of laticiferous vessels (NR), and mean distance between consecutive rings of the laticiferous vessels (MD). The individual statistical analyses and repeated measurements were performed through mixed linear models using the REML/BLUP (Restricted Maximum Likelihood/Best Linear Unbiased Prediction) procedure. Genetic and phenotypic correlations were also estimated. The accuracy estimates (Aˆc) for the traits in the two locations were higher (> 0.7), indicating good perspectives in a breeding program. The coefficient of genetic variation (CVg %) showed low variation between the sites: BT (4.5–7 %), NR (14.1–18.3 %), and MD (15–18.2 %). The NR expressed higher heritabilities and was therefore the best trait of the laticiferous system for predicting genetic values; it showed expressive genetic correlations with RY, and may be used in indirect selection. BT did not show progeny × height interaction, indicating that the classification of the progenies was the same, regardless of the tree height at collection. To select progenies in common in the young and adult ages, using analysis of measurements repeated in time, the most suitable height for collection of samples in the adult progenies for the traits of the laticiferous system was up to 80 cm. The traits of the laticiferous system collected at 30 cm in young progenies are associated with RY, both in the youth phase and in the adult phase. They can be used to assist in early or indirect selection of rubber tree progenies.
Keywords: Early selection; Genetic correlations; Hevea brasiliensis; REML/BLUP